1970
DOI: 10.3126/nje.v1i2.5141
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Asymptomatic Bacteriuria among Women with Vesico-Vaginal Fistula in South-Eastern Nigeria

Abstract: Objective Vesico-vaginal fistula (VVF) involves the pathological communication between the urinary bladder and vagina, possible complications arising from urinary tract infection merits consideration. This study seeks to evaluate significant bacteriuria among VVF clients. SettingThe setting was the South east Fistula Centre, Abakaliki, Ebonyi State, Nigeria. PopulationThis was a total population study of all consenting HIV negative VVF clients. MethodThis cross-sectional study assessing asymptomatic bacteriuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
4
14
3
Order By: Relevance
“…In general, the overall prevalence of UTI in the present study was 58.1%, which is almost similar with other report from India (60%) [ 19 ]. But the present finding of UTI was lower than other studies from Libya (65.7% ) [ 20 ] and Nigeria (76.1%) [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In general, the overall prevalence of UTI in the present study was 58.1%, which is almost similar with other report from India (60%) [ 19 ]. But the present finding of UTI was lower than other studies from Libya (65.7% ) [ 20 ] and Nigeria (76.1%) [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the overall prevalence of UTI was 28 (52.8%) which is almost similar with other report in Nigeria (76.1%) [17]. But this finding was higher than other studies in Kenya 8.0% [18] and Nigeria 11 (9.2%) [19]. The prevalence of UTI in the present study was also higher than another reports from pregnant women in the study area [20], Addis Ababa Ethiopia [21] and Tanzania [22].…”
Section: Discussionsupporting
confidence: 89%
“…Similar organisms as obtainable in this study have also been implicated as microorganisms associated with urogenital tract of VVF patients in North-West Nigeria. 5 In another study, Adaoye et al, 17 also reported similar pathogens as causative factors in asymptomatic bacteriuria amongst women with VVF. The antimicrobial susceptibility test results of K. pneumoniae isolated from urine samples of presurgery VVF patients showed that some of the most frequently used antibiotics including cotrimoxazole, tetracycline, amoxicillin, amoxicillin-clavulanic acid, ofloxacin and cefuroxime encountered resistance levels in excess of 50 % to all the K. pneumoniae isolates with the exception of ofloxacin where the resistance level was 44 %.…”
Section: Discussionmentioning
confidence: 99%
“…And these results concur with those of other researchers in Nigeria who reported varying levels of resistance and susceptibility patterns amongst bacterial organisms isolated from urine samples of pre-and post-surgery VVF patients. 5,17 CONCLUSION: Conclusively, this study has presumptively shown that K. pneumoniae, E. coli, S. pyogenes and S. aureus are common bacterial isolates prevalent in women with VVF conditions. And the antibiogram of these organisms to various conventional antibiotics showed that the bacteria exhibit varying levels of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation